Structure and biological activities of lipochitooligosaccharide nodulation signals produced by Bradyrhizobium japonicum USDA 138 under saline and osmotic stress - Muñoz, Nacira Belen (2014)
The establishment of a symbiotic interaction involves a signal exchange between the host legume (flavonoids) and the nitrogen-fixing rhizobia (nodulation factors (NFs)). Likewise, abiotic stress conditions, such as salinity and drought, strongly reduce the nodulation process, possibly affecting also the signal exchange. In this work we characterized the structure and biological activity of NFs produced by Bradyrhizobium japonicum USDA 138 under control, salt, and osmotic stress conditions. This strain is the most widely used in Argentine soybean culture; under control conditions, it produces a mixture of four types of NFs (V(C16:0,MeFuc), V(C18:1,MeFuc), IV(C18:1), and V(C18:1,Ac,MeFuc)). Interestingly, under stress conditions, this strain produces new types of NFs, one common for both stress conditions (V(C16:1,MeFuc)) and another one only present under salt stress (IV(C18:1,MeFuc)). All mixtures of NFs, extracted from control, salt, and osmotic stress conditions, showed biological activity in soybean plants, such as root hair deformation, and the radical application of purified NFs induced systemic differences in dry matter accumulation. The inoculation of soybean with genistein-induced bacteria cultured under both control and stress conditions had a positive effect on the number of nodules formed and in some cases on dry matter accumulation. These responses are not related to changes in chlorophyll fluorescence or greenness index.